1996
DOI: 10.1111/j.1600-0447.1996.tb10649.x
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐observer and test‐retest reliability of the Italian version of the Karolinska Psychodynamic Profile in two groups of psychiatric patients

Abstract: A total of 64 psychiatric patients were tested with the Italian version of the Karolinska Psychodynamic Profile in order to investigate interobserver and test-retest reliability. The mean inter-observer agreement coefficients (rho) ranged from 0.75 to 0.80 with less experienced psychiatrists, while the mean rho value was higher (0.96) with more experienced raters. Test-retest values were good, ranging from 0.53 to 0.93. Overall, reliability was comparable with that reported in the original Swedish study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
1
15
1
Order By: Relevance
“…The results indicated that judges with more training in psychodynamic psychotherapy obtained better reliability [5]. Similar results have also been found by Turrina et al [7], who found that interviewers with better training and more psychodynamic experience obtained better reliability. In the present study, the interviewers had a great deal of clinical experience in psychodynamic psychotherapy, whereas the reliability judge had not.…”
Section: Discussionsupporting
confidence: 79%
See 4 more Smart Citations
“…The results indicated that judges with more training in psychodynamic psychotherapy obtained better reliability [5]. Similar results have also been found by Turrina et al [7], who found that interviewers with better training and more psychodynamic experience obtained better reliability. In the present study, the interviewers had a great deal of clinical experience in psychodynamic psychotherapy, whereas the reliability judge had not.…”
Section: Discussionsupporting
confidence: 79%
“…The results of the present study, as well as those of other KAPP reliability studies, indicate that this is the case [6, 7, 8]. In the present study, neither the interviewers nor the reliability judge worked in the setting were the KAPP was constructed, nor were they trained by its developers.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations